Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien Rawat Jalan di Rumah Sakit TK III Dr. R. Soeharsono Banjarmasin - Ihsan Ridhoni Fawwaz; Merlin Karinda; Muhammad Noor Aditya Pratama; Novita Dwi Widiya Ningsih (STIE PENA, 2026)
Quality healthcare is an important factor in improving patient satisfaction. This study aims to determine the effect of service quality on outpatient satisfaction at TK.III Dr. R. Soeharsono Hospital in Banjarmasin. The study used a quantitative design with a survey method. The population consisted of 183 outpatients, and based on the Slovin formula, 65 respondents were selected as the sample using purposive sampling. Primary data were collected through a questionnaire that had been tested for validity and reliability, while the data were analyzed using simple linear regression with the help of SPSS. The results showed that most respondents rated the quality of services in the good category. Regression testing produced a significant positive coefficient (p-value < 0.05), indicating a significant effect of service quality on outpatient satisfaction. The coefficient of determination (R²) showed that the service quality variable contributed to the variation in patient satisfaction, while other factors outside this study may also influence satisfaction. In conclusion, service quality has a positive and significant effect on outpatient satisfaction at TK.III Dr. R. Soeharsono Hospital in Banjarmasin. Therefore, improvements in service quality, especially in the aspects of facilities, service speed, and the friendliness and responsiveness of healthcare staff, should continue to be enhanced to achieve the national minimum service standards and meet patient expectations.